A hybrid descent method for the two-edge disjoint survivable network design problem with relays. (October 2017) - Bouchakhchoukha, Adel; Hifi, Mhand
Highlights: A new hybrid descent method is proposed for tackling a spacial Network Design Problem with Relays. A decomposition strategy is used for combining neighborhood search and a modified descent procedure. The new hybrid algorithm succeeds in yielding new solutions on benchmark instances of the literature. Abstract: In this paper, we propose a hybrid descent method for solving a special case of the well-known network design problem with relays; that is, the two-edge disjoint survivable network design problem with relays. Such a problem arises in several applications related to telecommunications and distribution networks. The proposed method can be viewed as a two-stage approach, where an intensification neighborhood search and a modified descent method are applied. The neighborhood search is used either for improving the quality of the solutions or merging two sub-solutions composed of partial and complementary ones. The descent method uses degrading and rebuilding strategies in order to reach a series of solutions. The performance of the method is evaluated on benchmark instances taken from the literature, where its provided results are compared to those reached by the best methods available in the literature. The obtained results show that such a method is able to provide new solutions.